A Closer Look on English Language Education Department Students' Contention of Using Mind Mapping Techniques - Sri Rejeki Murtiningsih; Delviana Rahma Dania; Sibakhul Milad Malik Hidayatulloh (VELES Voices of English Language Education Society, 2022)
Teachers and students have widely used mind-mapping techniques to enhance teaching and learning experiences in education. This study intended to explore the benefits and challenges of applying mind-mapping techniques based on students' perceptions. The current study used a qualitative approach. In-depth interviews were employed to collect the data. The study involved four students in their junior year of an English Language Education Department of a private university who had frequently used mind mapping. All participants in the study viewed that mind mapping positively contributed to their English learning. The contributions included saving time, assisting them in learning and understanding materials, and recalling materials more easily. In addition, the participants also claimed that mind mapping enhanced their creativity in learning, helped them brainstorm ideas, improved language skills, increased their interests, and motivated students to learn. Apart from the benefits, all participants considered mind-mapping techniques challenging due to their complexity, especially when they were new to mind-mapping. In addition, they also believed that applying mind-mapping techniques consumed much time. The study concluded that mind mapping positively contributed to students' learning experiences, especially in organizing the information they gained when learning.